The economic Indicators of digitalization technologies in the agricultural production, food industry and marketing sectors - a review: Indicators of digitalization technologies in the agricultural production, food industry and marketing sectors - a review - Al Tamimi, Abbas (University of Thi-Qar Journal of agricultural research, 2024)
Some Arab countries have faced many problems in the growth of the economy, which depends largely on agricultural production, food industries, marketing and electronic commerce. This review came to extract the most important advantages and obstacles to the application of digitalization techniques in the agricultural production sector, food industries, and electronic marketing to identify them in a deductive manner. It has become clear that the most important obstacles facing the application of digitization are the legal legislation related to the application of digitization techniques, as well as digital illiteracy in rural society in particular, in addition to the deterioration of the infrastructure necessary for the application of digitization techniques. It recommended that a long-run strategy developed to apply digitalization techniques in agricultural production, food industries, marketing and electronic commerce. As well as developing human capital, especially in rural areas, to provide an appropriate technical environment to achieve development in agricultural production and food industries to contribute to economic growth